2014
DOI: 10.1111/bph.12701
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ peptide receptor antagonist JTC‐801 reverses pain and anxiety symptoms in a rat model of post‐traumatic stress disorder

Abstract: BACKGROUND AND PURPOSESingle-prolonged stress (SPS), a rat model of post-traumatic stress disorder (PTSD), also induces long-lasting hyperalgesia associated with hypocortisolism and elevated nociceptin/orphanin FQ (N/OFQ) levels in serum and CSF. Here, we determined the effect of JTC-801 (N-(4-amino-2-methylquinolin-6-yl)-2-(4-ethylphenoxymethyl) benzamide monohydrochloride), a nociceptin/orphanin FQ peptide (NOP) receptor antagonist, on symptoms of pain and anxiety in rats after SPS exposure, and examined N/O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 68 publications
(120 reference statements)
6
44
1
Order By: Relevance
“…Because the NOP system is widely implicated in stressrelated pathophysiology (Zhang et al, 2012b(Zhang et al, , 2015 and recent evidence suggests that cykokines can also regulate mood and psychologic responses to stress (Zhu et al, 2010;Moretti et al, 2015), a better understanding how NOP cytokine signaling, extended into nonimmune cell types, will prove critical as we attempt to understand how NOP signaling functions to bidirectionally regulate the stress response.…”
Section: Nociceptin Opioid Peptide Receptor and Inflammatory Signamentioning
confidence: 99%
“…Because the NOP system is widely implicated in stressrelated pathophysiology (Zhang et al, 2012b(Zhang et al, , 2015 and recent evidence suggests that cykokines can also regulate mood and psychologic responses to stress (Zhu et al, 2010;Moretti et al, 2015), a better understanding how NOP cytokine signaling, extended into nonimmune cell types, will prove critical as we attempt to understand how NOP signaling functions to bidirectionally regulate the stress response.…”
Section: Nociceptin Opioid Peptide Receptor and Inflammatory Signamentioning
confidence: 99%
“…BPN has low affinity for ORL-1 receptors, and we did not observe diminished activity of BPN's effects in the FST following systemic administration of JTC-801. At this dose JTC-801 is known to diminish allodynia and hyperalgesia in mice and reverse stress-induced behavioral deficits (Delaney et al, 2012;Yamada et al, 2002;Zhang et al, 2015). Numerous studies have shown that activation of ORL-1 receptors produces anxiolytic effects, whereas antagonism evokes antidepressant-like responses (Witkin et al, 2014).…”
Section: Oprd1mentioning
confidence: 99%
“…SPS is mainly used in rats. SPS elicits a deficit in fear extinction retention (Knox et al, 2012), has been shown to present enhanced N/OFQ levels in the hippocampus, cerebrospinal fluid and changes in allodynia and hyperalgesia (Zhang et al, 2014). …”
Section: Implications Of N/ofq-nop Receptor In Human Brain Disordementioning
confidence: 99%